Citizens lack access to healthcare facilities: How COVID‐19 lockdown and social distancing policies boost roadside chemist businesses in South‐Eastern Nigeria. (2nd September 2021) - Iwuoha, Victor Chidubem; Aniche, Ernest Toochi; Obiora, Charles Arinze; Umeifekwem, Uchenna T.
Abstract: This study examines how COVID‐19 lockdown and social distancing policies impacted on citizens' access to healthcare facilities and the level of patronage of chemist/pharmacies for self‐treatment. A cross‐sectional questionnaire survey method was used to collect data by asking individuals quantitative and qualitative questions in person which included 6 structured open‐ended questions. Participants include operators of purposively selected three classes of small businesses/self‐employed services in South‐Eastern Nigeria. This involves 120 fashion/event related businesses, 80 food related businesses and 100 general merchandise–a total of 300 small businesses. Quantitative data were analysed by frequencies and descriptive statistics while qualitative data were analysed using thematic/content analysis. It concludes that although COVID‐19 lockdown policies are generally perceived to have negative effects on small businesses, these policies have particularly had positive effects on the chemist/pharmacies businesses compared with other small businesses. About 85% increase in patronage of chemist businesses compared with 63.7% decline in patronage of other small businesses is essentially linked to increasing rate of self‐medication as a result of government's poor implementation of COVID‐19 public health policies amidst lockdown measures–which limited people's access to hospitals and healthcare centres. The study proposes reformed pandemic‐lockdown policies to increase people's access to healthcare services and reduce overreliance on self‐medication and excessive patronage of roadside chemist/pharmacies.